ARISTOTLE’S TRIAD OF PERSUASIVENESS IN ENGLISH LANGUAGE WRITERS' WRITTEN TEXT - Wan Hurani Osman; Mohammad Aqmal Hafidz Musa; Sabariah Abd. Rahim; Bernadette Tobi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In order to convince someone of what one is saying or writing about, the use of the appropriate persuasive technique is very important. At tertiary education level, academics who focus on teaching communication either in the written or spoken form emphasises on being persuasive. In communication, either in daily activities, academic or workplace, persuading someone is often used. The sender of the message needs to persuade the receiver to believe, agree, acknowledge and obey the message that one wants to convey. In this study, Aristotle’s triad of ethos, pathos, and logos is usually used to explore whether a text is persuasive. Aristotle's triad focuses on credibility (ethos), emotion (pathos), and facts (logos) in persuading a person on a certain issue that is being presented. The present study attempts to identify how ESL writers write to persuade. Samples of English as Second Language writers’ written assignments produced for an English for Occupational Purpose Module are used in this study. The assignment is in the form of a proposal paper written to propose an activity. The objective of a proposal paper is to propose an idea, and it is written in the hope of persuading the person reading the proposal to agree, approve and support the proposal. By studying the use of Aristotle’s triad of persuasive appeals, it is hoped that it will assist academicians to focus on what to teach in their communication class and to be able to produce competent ESL writers who are able to persuade and make one agree with their ideas and issues.